(untitled) (Journal of Parents and Teachers, 2014)
Andrés Manjón (1846-1923) was a professor at the University of Granada and a priest who founded schools where all children could be educated. He oriented education towards the life of work, using games as a method of learning, as he criticized the fact that they were training "parrots" instead of men who thought and worked. His schools focused on children having fun while learning. His teaching methods focused on intuition, activity and consideration, and teachers were the main axes of education.